Facultative anaerobic bacteria on dentistry students’ gutta-percha points: The importance of disinfection (2018)
Background: During endodontic treatment in dentistry, if the gutta-percha points contain microorganisms that are resistant to the conditions in the root canal once it is sealed, they can lead to new infections. The purpose of this study was to determine